Mencermati Fenomena Hot Money dan Potensi Kembalinya Krisis Ekonomi - Agung Waluyo (Universitas Bunda Mulia, 2017)
Short term investment or commonly called hot money last view days looklikes flowing Indonesian finance market also increase the volume. This short term investment flow in irregular and keeping many obligation letter in Indonesian, especially in certificated of Bank Indonesia, obligation and other securities investment in stock market. Consider this hot money resource has easy in and out, so competition of total amount foreign capital in the economic nation will result a chaos.Basicly it can called economic crisis has a closed relationship with the fragile factors, in federal resource the composition of te taxation, banking industry, the structure of banking industry and the corporation sector.Key words : Hot Money(Short Term Invstment), Economic Crisis